A graphical method for carbon dioxide emissions reduction in multi–product plants - Yap, Jane Y. (Animo Repository, 2020)
Carbon dioxide emissions reduction has been a common trend for many industrial processes in recent years. However, few analytical tools have been developed for visualising CO2 emissions reduction and supporting decisions at the enterprise level. A graphical technique known as Carbon Emission Composite Curves was developed previously, but was limited to the production of single product. In this work, the CO2 emissions reduction procedure is focused and extended to multi-product plants, in which CO2 emissions of shared and dedicated facilities of the production line are analysed. For cases where the carbon intensity of shared facilities is higher than that of the dedicated facilities, CO2 emissions reduction should focus on the shared facilities, before efforts are put forward for the dedicated facilities. In contrast, when the carbon intensity of dedicated facilities is higher than that of the shared facilities, it is necessary to explore ways to reduce CO2 emissions of the dedicated facilities. Two case studies are used to illustrate the procedure. © 2019 Institution of Chemical Engineers